Potential pathogenic and protective genotypes and phenotypes of vitamin D binding protein in multiple sclerosis - Al-Shammri, Suhail; Chattopadhyay, Arpita; Mustafa, Abu Salim (Frontiers in Neurology, 2025)
BackgroundThe main carrier protein of vitamin D and its metabolites in plasma is vitamin D binding protein (VDBP) or group-specific component (Gc). Two single nucleotide polymorphisms, rs7041, and rs4588 in the GC gene result in three major VDBP/Gc genotypes, GC1F (c.1296T, c.1307C), GC1S (c.1296G, c.1307C), GC2 (c.1296T, c.1307A), and phenotypes, Gc1F (p.432Asp, p.436Thr), Gc1S (p.432Glu, p.436Thr), and Gc2 (p.432Asp, p.436Lys). This study investigated frequencies of GC genotypes and phenotypes in Kuwaiti multiple sclerosis (MS) patients and healthy controls, and their associations with serum levels of 25 hydroxyvitamin D [25(OH)vitamin D] and VDBP.MethodsThe genomic DNA was isolated from blood samples of drug-naïve MS patients (N = 151) and controls (N = 127). DNA regions covering the targeted mutations were amplified by PCR, sequenced by the Sanger method, and analyzed to determine GC genotypes and phenotypes. Serum 25(OH)vitamin D and VDBP levels were measured by enzyme immunoassay. SPSS used for statistical analyses. Differences between independent and related groups tested by Mann–Whitney U and Wilcoxon signed-rank tests respectively, Genotype and phenotype frequencies were calculated; p < 0.05 considered significant.ResultsThe study detected four Gc genotypes/phenotypes, namely GC1F/Gc1F (c.1296T, c.1307C/p.432Asp, p.436Thr), GC1S/Gc1S (c.1296G, c.1307C/p.432Glu, p.436Thr), GC2/Gc2 (c.1296T, c.1307A/p.432Asp, p.436Lys), and GC3/Gc3 (c.1296G; c.1307A/p.432Glu, p.436Lys) in both subjects. The frequencies of GC3 genotype (control: 5.51%; patient: 28.48%) and Gc3-containing phenotypic groups (Gc1S/Gc3 + Gc2/Gc3 + Gc3/Gc3) were significantly higher in patients. Moreover, frequencies of GC1F genotype (control: 27.17%; patients: 5.30%) and Gc1F-containing phenotypic groups (Gc1F/Gc1F + Gc1S/Gc1F + Gc2/Gc1F) were higher in controls. Vitamin D levels were deficient in both groups. However, VDBP concentrations were significantly low in MS patients only.ConclusionThe VDBP/GC genotypes and phenotypes are associated with MS. Common genotype GC1F might be protective, and GC3, the novel variant found in MS patients appeared to be pathogenetic. Hypovitaminosis-D is prevalent in MS patients and controls.